2017
DOI: 10.1016/j.chroma.2016.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the peak resolution and the stationary phase retention between the satellite and the planetary motions using the coil satellite centrifuge with counter-current chromatographic separation of 4-methylumbelliferyl sugar derivatives

Abstract: Coil satellite centrifuge (CSC) produces the complex satellite motion consisting of the triplicate rotation of the coiled column around three axes including the sun axis (the angular velocity, ω1), the planet axis (ω2) and the satellite axis (the central axis of the column) (ω3) according to the following formula: ω1 = ω2 + ω3. Improved peak resolution in the separation of 4-methylumbelliferyl sugar derivatives was achieved using the conventional multilayer coiled columns with ethyl acetate/1-butanol/water (3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…On the other hand, in the rotation speed combination types III and IV, extremely low stationary phase retention was obtained even by increasing the revolution speed. This tendency was same as the results obtained in our previous studies [1,10]. From these results, it was revealed that the peak resolution and the stationary phase retention were affected by the rotation speed combination ratio more than by the revolution speed when using the conventional multilayer coiled column.…”
Section: Reinforcement Of the Csc Instrument And Csc Separation Of 4-supporting
confidence: 89%
See 4 more Smart Citations
“…On the other hand, in the rotation speed combination types III and IV, extremely low stationary phase retention was obtained even by increasing the revolution speed. This tendency was same as the results obtained in our previous studies [1,10]. From these results, it was revealed that the peak resolution and the stationary phase retention were affected by the rotation speed combination ratio more than by the revolution speed when using the conventional multilayer coiled column.…”
Section: Reinforcement Of the Csc Instrument And Csc Separation Of 4-supporting
confidence: 89%
“…The CSC instrument used in the present studies was fabricated at the Machining Technology Center of Nihon University (Chiba, Japan). The design of the CSC instrument has been described in detail elsewhere [1], while the side motor was replaced with the more powerful one [10].…”
Section: Apparatusmentioning
confidence: 99%
See 3 more Smart Citations